Sistema de control interno y su relación con la gestión de los bienes estatales de la Universidad Nacional de la Amazonía Peruana sede Requena 2023 - Iturraran Sandoval, Edgar David (2025)
The purpose of this study was to determine the relationship between the implementation of an internal control system and the management of state assets at the National University of the Peruvian Amazon, Requena, 2023. A basic type of research with a quantitative approach and non-experimental design was used, applying structured questionnaires to a sample of 50 public managers assigned to areas linked to the management of state assets. The results showed that in the internal control system variable, the majority of the workers report that internal control is almost always carried out (40%), while a smaller percentage indicate sometimes (32%) and always (28%). This indicates that the perception of control in the entity is at a high level. For the variable management of state assets, the results showed that the majority of workers report that they perform internal control almost always (72%) and 28% always; this indicates that the perception of both variables is at a high level. Also, according to the chi-square test, there is a significant relationship between these variables with a sig. of 0.001, which allowed the null hypothesis to be rejected and the general alternative hypothesis to be accepted. This confirms that the greater the control, the greater the direct impact on the management of state assets, which is consistent with the findings of international and national studies.